Monitoring Bpm and Body Temperature Based Internet of Things (IoT) Thing speak Platform - Romadhini, Novita Nur Azize; Kholiq, Abdul; Rahmawati, Triana; Masood, Faraz (Jurnal Teknokes, 2023)
Technological advancements in the field of healthcare, coupled with contemporary scientific and technological progress, have led to significant advancements in various operational procedures within medical institutions. These advancements include the adoption of automated systems in lieu of human intervention. An example of this progress is the implementation of automated systems for monitoring individuals' heart rates and body temperatures. Heart rate and body temperature stand as critical indicators employed by medical professionals to assess both physical and mental well-being. Deviations from normal heart rate and body temperature values can signify underlying issues. Body temperature, specifically, can offer insights into internal bodily conditions. This transition to automated monitoring tools has resulted in heightened practicality and efficiency. These tools offer real-time monitoring capabilities and the option for remote oversight. The monitoring device's architecture employs the Max30102 as a BPM sensor, which boasts a digital output. Additionally, the MLx90614 sensor functions as a digital temperature sensor. The collected data is then processed and showcased on an I2C LCD screen, with information transmitted to the ThingSpeak platform via the ESP32, serving as a Wi-Fi module. Notably, the BPM sensor demonstrates a minimal error rate of 0.23% and a maximum of 2.11%, while the temperature sensor showcases a minimal error rate of 0.59% and a maximum of 3.37%. The outcomes of this research exhibit potential application in enhancing the efficiency of remote monitoring systems when integrated into patient monitoring setups.